EVALUATION OF ROLE OF FICUS BENGALENSIS IN MODULATION OF COGNITIVE IMPAIRMENT AND OXIDATIVE STRESS IN DIABETIC RATS - SURANAGI, UMESH D; ARORA, ANKIT; GOGOI, SANJIB; NIRALA, RAVIKANT; SOLANKI, BHUPINDER (Asian Journal of Pharmaceutical and Clinical Research, 2022)
Objectives: Our objective was to study the effects of Ficus benghalensis on cognitive behavior and oxidative stress in diabetic rats and to compare with vitamin C and glimepiride. Methods: Wistar rats of either sex randomized into five groups of diabetic rats by streptozocin (STZ), five groups of non-diabetic rats (distilled water) (n=10). Subgroup division (F. benghalensis dose I and II, i.e., 50 mg/kg and 100 mg/kg; Vitamin C 100 mg/kg and glimepiride 0.5 mg/kg) were done. Each drug was given to one diabetic and one non-diabetic group. Other set served as control. Assessment of blood glucose, cognitive function (using continuous avoidance apparatus and Morris water maze test), and oxidative stress (measuring Malondialdehyde (MDA), reduced glutathione (GSH) levels) were done on Day 0 and 30. The acquisition phase of cognitive behavior tests was assessed on 0, 14, and 29 days and retention phase was assessed on 1, 15, and 30 day. Results: As compared to control group, F. benghalensis dose I, dose II, and glimepiride showed significant decrease (p<0.001) in blood glucose. F. benghalensis dose I, dose II, vitamin C, and glimepiride group showed significant decrease in acquisition and retention of transfer latency on 29 and 30 days. Significant increase in retention of step-down latency on 30 day was shown by both the doses of F. benghalensis. Both doses of F. benghalensis, vitamin C and glimepiride group showed significant increase in retention of Quadrant-time in comparison to control on 30 days. Significant decrease in brain MDA levels while a significant increase in brain GSH levels was observed in all groups except control. Conclusion: F. benghalensis reverses behavioral and biochemical changes induced by STZ and effects are comparable with that of vitamin C and glimepiride.